Analyzing spatiotemporal relationship between land use changes and groundwater quantity in Hamadan north plains - Hossein Rafieemehr; Lotfali Kozegarkaleji (علوم محیطی)
Introduction: Groundwater is considered the most important source for various uses in arid and semi-arid regions. Thus, evaluating the effects of human activities such as changes in land use/cover on groundwater resources plays a vital role in sustainable water management and, therefore, spatial planning. Accordingly, the need to integrate land use planning and water resources management is widely emphasized. In addition, perceiving the spatio-temporal relationship between land use changes and groundwater resources is crucial for the sustainable management of the plains in Iran. The present study aimed to assess this relationship in the Hamedan-Bahar Plain.Material and methods: In the study, the land use maps of 1989, 1997, 2005, 2013, and 2018 were prepared from Landsat satellite images, categorized, and evaluated with respect to accuracy. Further, six uses including irrigated and dry agricultural lands, rangelands and elevations, man-made areas, gardens, and surface water resources were extracted and classified. Furthermore, the distribution maps for groundwater depth were prepared through kriging for five years based on the piezometric data. Finally, the correlation and relationship between land use changes and groundwater depth fluctuations were determined by the REGRESS method.Results and discussion: The land use maps demonstrated an increase in the share of rangelands and elevations (9.68% in 1989 to 40.85% in 2018) and their conversion to dry agricultural lands. Additionally, the share of man-made and irrigated agricultural lands increased from 1.27 to 2.45% and 5.32 to 6.25% during the timespan, respectively. The trend of changes in groundwater level was more evident in the flatbed of the plain, in which groundwater level was less than 1800 m and important habitats and irrigated agricultural lands were available. In addition, the average annual depletion of groundwater level for a 29-year time span was 0.91 m, and the minimum and maximum of the R–value related to five study periods was obtained 0.36 and 0.40 based on the REGRESS method, respectively. Further, the role of managerial factors should be considered as well as the relative relationship between groundwater level changes and land use. Furthermore, the correlation between the decrease in groundwater level and land use in each period relatively increased compared to the previous one by representing an R-value of 0.40 during 1989-2018, which can explain almost 16.2% of their changes. Due to the water resource scarcity, land use should be planned based on the scale, power, and extent of plains and watersheds in order to attain a sustainable regional water system.Conclusion: The results of the study can play an important role in understanding the importance of groundwater resources and emphasize the necessity of paying more attention to the effects and changes of land use on groundwater in arid and semi-arid regions. Additionally, the results indicated the sensitivity of groundwater, as the most important water resource in the plains located in arid and semi-arid regions, to the types of variations. Decreasing rangelands, gardens, aqueduct, and surface water-dependent thickets as well as expanding dry and irrigated agricultural and man-made lands are regarded as some of the factors reducing groundwater level in the region. It is worth noting that these factors should be integrally evaluated with respect to other factors such as irrigation systems, water pricing, cultivation pattern, agricultural economics, and an increase in runoff.